Spectral Characterization, DNA Binding and Antibacterial Studies of Heterolyptic Metal Complexes with 2-Acetylthiophene-4-phenyl-3-thiosemicarbazone and 2,2′-Bipyridyl - Srinivasulu, K.; Hussain Reddy, K.; Dhanalakshmi, D.; Anuja, K.; Nagamani, Y.B. (Asian Journal of Organic & Medicinal Chemistry, 2021)
Heterolyptic metal complexes having the composition M(Bpy)Cl2 (where, M = Cu(II), Ni(II) and Co(II); Bpy = 2,2′-bipyridyl) were reacted with 2-acetylthiophene-4-phenyl-3-thiosemicarbazone (ATPT) to produce bivalent metal complexes with molecular formula M(Bpy)(ATPT)Cl·H2O. The complexes were characterized using physical (molar conductivity) and spectral (mass spectra, infrared and electronic spectroscopies) methods. Electrochemical behaviour of the complexes was revealed using cyclic voltammetry. The Cu(II)/Cu(I) couple complexes show a quasi-reversible cyclic voltammetric responses. The DNA binding properties of complexes were determined through absorption UV-visible spectrophotometry. Furthermore, the agar well diffusion method was used to screen the metal(II) complexes for their antibacterial activity against pathogenic bacterial strains, namely Gram negative strains such as Escherichia coli and Klebsiella pneumonia and Gram positve strains such as Staphylococcus aureus and Bacillus cereus. The synthesized Cu(Bpy)(ATPT)]Cl·H2O complex strongly inhibits bacteria compared with other complexes.